The Interaction Between Monetary and Macroprudential Policy to Achieve Price and Financial Stability: An Evidence from Indonesia - Nadia Restu Utami; Nia Yustiana; Ferinda Nafisa; Sigiro, Ely Elprida (Contemporary Public Administration Review, 2025)
The 1998 Asian Financial Crisis was a milestone in the existence of structural policy reforms in the Indonesian financial sector. Most of the empirical results show that the financial crisis was caused by the lack of soundness and instability of the financial sector. This problem changed the perspective of Bank Indonesia, the central bank in Indonesia, that financial stability is as important as price stability. This highlights the need for the central bank to also ensure financial stability, while monetary policy focuses on price stability and economic growth. However, achieving these goals does not always ensure financial stability. To address systemic risk, Indonesia has begun adopting macroprudential policies. Thus, monetary policy cannot secure both price and financial stability, and a policy mix with macroprudential measures is needed to achieve both price and financial stability. This research examines the relationship between monetary and macroprudential policies and their effects on stability. Monetary policy was measured by the BI Rate and macroprudential policy was measured by Loan to Value (LTV). Price stability was proxied by inflation, and financial stability by credit growth. We analyzed the causality between the variables using the Vector Autoregression Model (VAR) and Granger Causality Test, using quarterly time series data from 2005:Q1 to 2018:Q3. The findings indicate that monetary and macroprudential policies significantly affect price and financial stability. Empirical findings show that tightening the BI rate and LTV significantly reduces inflation and credit growth. This paper highlights the need for a policy mix to ensure price and financial stability.